18erios
contestada

which of the following is equivalent to the radical expression below when x≥7?
√x-7 *√x+1
A)√x^2-6x+7
B)√x^2-6x-7
C)√x^2+8x+7
D)√x^2+8x-7

Respuesta :

the answer
the main rule for a square root calculus is given by √A*√B  = √A*B, for all value positive of A and B

so we can extended the given value of the fonction as

√x-7 *√x+1  = √x-7 *√x+1 = √(x-7 )* (x+1) 

but the extended form of (x-7 )* (x+1)  is (x-7 )* (x+1) = x² + x -7x -7= x²-6x -7
therefore,  √(x-7 )* (x+1)  = √(x²-6x -7), the value which is equivalent to the radical expression is B)√x^2-6x-7, when x≥7
ACCESS MORE